Opportunistic tactical portfolio management using genetic algorithm and reinforcement learning - Chan, Janice Rui En (Nanyang Technological University, 2020)
Market trend reversals are what allow investors to capture profits, but stock trading comes with risks. A good portfolio is therefore one that can diversify risks yet exploit market trend reversals to maximize returns. This paper describes the use of 3 portfolio rebalancing strategies to explore the impact of base rates, commission rate loss and exchange rate loss on a portfolio’s profit level. The three rebalancing strategies are Opportunistic Tactical Buy and Hold Strategy, Genetic Algorithm Rebalancing Strategy (with risk algorithm) and Reinforcement Learning Rebalancing Strategy.